Prácticas de enseñanza de iniciación a la lecto-escritura en el nivel inicial II de una institución educativa ubicada en el Centro de Quito - Gallardo Ramírez, Doménica Michelle (2016)
The following case study shows the interest to know how they develop the "Practice teaching of beginning reading and writing at the initial level II of an educational institution located in the City Centre of Quito", data collected by the observation which was recorded through a field diary , observation records, interviews; It will allow us to obtain real data objectively contribution to research. For the development of the research has made an observation of two months to obtain relevant data useful for the development of this document. The data compiled in the process of gathering information are: planning, environment teacher interaction and deponent, execution of the process of learning, work organization and learning process, assessment strategies and academic tasks, using data obtained on the observation you may be contextualize the information obtained based on the matrix of the observation sheet, assessing the strengths detailing the findings if there are weaknesses to make a critical analysis covering positive and negative aspects.